The Effect of Sous-Vide Cooking Parameters, Chilled Storage and Antioxidants on Quality Characteristics of Atlantic Mackerel (Scomber scombrus) in Relation to Structural Changes in Proteins - Janna Cropotova; Revilija Mozuraityte; Inger Beate Standal; Kari Cecilie Aftret; Turid Rustad (Food Technology and Biotechnology, 2019)

(untitled)
The aim of the present study is to assess the influence of different sous-vide time-temperature regimes and use of two types of commercial antioxidants (rosemary extract and rosemary extract with ascorbyl palmitate) on quality parameters of Atlantic mackerel (Scomber scombrus) during chilled storage. The mackerel ﬁllets were treated with the antioxidants, exposed to sous-vide cooking at 70 and 80 °C for 10 and 20 min, and further stored for 1, 3, 9 and 15 days at (0±1) °C. Changes in dry matter and ash, cook loss, protein oxidation and solubility, as well as texture parameters in sous-vide cooked mackerel during storage, were assessed by application of multiple regression analysis. It was revealed that duration of chilled storage had the highest contribution to the decrease in cook loss due to a possible reabsorption of water released during cooking by unfolded proteins. At the same time, this parameter increased protein carbonylation in mackerel samples, resulting in a decreased protein solubility due to aggregation of proteins and subsequent toughening of the fish muscle. However, the use of antioxidants has shown to be highly efficient in decreasing the protein carbonylation in the analysed fish samples.